Using ICT Tools in Learning English as a Professional Language - Diachok , Nadiia (Educological discourse, 2025)
A modern specialist in Ukraine must have a fairly high level of English. Today, the entire scientific world depends on the English language: scientific information, new developments, inventions and instructions, discussions and correspondence. The paper describes the features of using various ICT tools in the educational process when training students of humanitarian specialties. An overview of the advantages of using individual ICT tools is carried out in order to reveal their possibilities for learning English as a professional language. It is emphasized that today the use of various ICT tools in the process of studying English as a professional language is designed to help develop the student’s personality and motivate him to long-term study of the English language. The use of various ICT tools in the process of studying English as a professional language improves a number of competencies in students, such as: the ability to compare the advantages and disadvantages of information provided in different sources, the ability to choose the necessary technologies for searching for the necessary information, the creation and use of a model of studying and processing information. It is emphasized that ICT tools in the process of studying English as a professional language help the teacher to make language learning easier and more modern, closer to real conditions. The article emphasizes the need for a rational combination of the traditional form of the educational process and modern ICT tools in the process of studying English as a professional language. Examples of ICT tools that can be used in the educational process (in the process of studying English as a professional language) are offered. The possibility and expediency of monitoring and assessing students’ achievements through various ICT tools of students’ knowledge are described. It is concluded that the use of various ICT tools in the process of learning English as a professional language makes it possible to create an individual educational trajectory of the student.